Exploring the work values and workspace preference of government employees in Koronadal City - Machan, Jaime Andrea E (2020)
This research generally focuses on determining the workspace preferences of government employees in relation to their work values. A wide body of research has explored the links between the person and their environments, and their degree of match or correspondence. Environmental Psychology, and the theories Person-Environment Fit and Work Adjustment are utilized, which suggests that in the concept of fit or misfit of person and environment, the work environment should be explored not only in its psychosocial influences but also as a physical space where tasks are performed which influences work outcomes (Vischer, 2006). For the purpose of this study, the person component is represented by the government employees defined by their work values, and the environment component is represented by the physical attributes of the workspace. Their work values were measured using Minnesota Importance Questionnaire. On the other hand, the physical space was assessed through the IEQ factors, evaluated by the researcher and the respondents, respectively. Applying Kano?s model of satisfaction in the factors, multiple regression analysis was conducted. The study concluded that the top four work values of the government employees surveyed are Achievement, Safety, Comfort, and Autonomy. Ease of interaction, amount of space, sound privacy, visual comfort, amount of light, comfort of furnishings, colors and textures, and visual privacy are the architectural aspects to be highly prioritized in designing work spaces according to the prevailing work values of the respondents.